The impact of uncertainty on professional exchange rate forecasts - Joscha Beckmann; Robert Czudaj (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This paper analyzes the role of uncertainty on both exchange rate expectations and forecast errors of professionals for four major currencies based on survey data provided by FX4casts. We consider economic policy, macroeconomic, and financial uncertainty as well as disagreement among CPI inflation forecasters to account for different dimensions of uncertainty. Based on a Bayesian VAR approach, we observe that effects on forecast errors of professionals turn out to be more significant compared to the adjustment of exchange rate expectations. Our findings are robust to different forecasting horizons and point to an unpredictable link between exchange rates and fundamentals. Furthermore, we illustrate the importance of considering common unpredictable components for a large number of variables. We also focus on the post-crisis period and the relationship between uncertainty and disagreement among exchange rate forecasters and identify a strong relationship between them. – – Dieser Beitrag analysiert die Bedeutung von Unsicherheit für professionelle Wechselkurserwartungen und die resultierenden Prognosefehler für vier große Währungen auf Basis von Umfragedaten von FX4casts. Wir betrachten politische, makroökonomische und finanzielle Unsicherheit sowie die Inflationsunsicherheit als unterschiedliche Dimensionen von Unsicherheit. Basierend auf einem Bayesianischen VAR-Modell finden wir, dass eine Steigerung von Unsicherheit oftmals den Prognosefehler erhöht. Die Auswirkungen auf die Prognosefehler sind im Vergleich zu der Anpassung der Wechselkurserwartungen wesentlich bedeutsamer. Die Ergebnisse sind robust über unterschiedliche Prognosehorizonte und bestätigen einen nicht prognostizierbaren Zusammenhang zwischen Wechselkursen und Fundamentaldaten. Erwartungsunsicherheit ist zudem insbesondere nach der Finanzkrise stark mit den Unsicherheitsmaßen korreliert.
Keywords: F31; F37; 330; Bayesian VAR; exchange rates; expectations; forecast; uncertainty